The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1167/iovs.06-0766
|View full text |Cite
|
Sign up to set email alerts
|

Is Pseudophakia a Risk Factor for Neovascular Age-Related Macular Degeneration?

Abstract: The results do not support the hypothesis that pseudophakia is a major risk factor for the development of neovascular AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…Similar numbers of increased incidences of early or late AMD from 5 to 15 years after cataract surgery were published in other large epidemiological studies [29,30,31], except one [28]; Wang et al [27] reported an OR of 5.7–7.3 for late AMD incidence in pseudophakic patients after 5 years.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar numbers of increased incidences of early or late AMD from 5 to 15 years after cataract surgery were published in other large epidemiological studies [29,30,31], except one [28]; Wang et al [27] reported an OR of 5.7–7.3 for late AMD incidence in pseudophakic patients after 5 years.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, an increased longtime risk of AMD or AMD progression was found for pseudophakic patients in several large epidemiological trials following patients for 5–15 years after cataract surgery [25,26,27,28,29,30,31,32,33]. Concerning quantitative AMD changes after cataract surgery, no large or prospective studies have been published so far.…”
Section: Introductionmentioning
confidence: 93%
“…It suggests that the development of cataract or cataract surgery did not markedly influence the development of age-related macular degeneration. Both these studies, however, are contradictory to a number of studies, including an investigation of autopsy eyes [36], several case series [37][38][39], and population-based epidemiologic studies [23,24,[40][41][42], in which concerns were raised with regard to the potential of cataract surgery to accelerate progression to advanced, vision-threatening forms of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Both conditions are quite common in the elderly and have overlapping symptoms, and deciding when to perform cataract surgery in patients with AMD can be difficult at best. Some clinicians believe that cataract surgery is beneficial in AMD patients whereas others fear that surgery could have deleterious effects; conflicting results from retrospective studies have led to further confusion regarding this issue (Kaiserman 2007;Sutter 2007).…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%